Architectural Record 1942-1967 - Phoebus Ilias Panigyrakis (A+BE: Architecture and the Built Environment)
This PhD thesis examines the editorial policies and publishing history of the American periodical Architectural Record in the quarter century from 1942 to 1967. Operating since 1891, the Architectural Record is the longest-living and most circulated professional magazine of architecture, with a strong and lasting impact on the development of the discipline and the profession in the US and abroad. As an archive of architectural knowledge, its history during the mid-20th century is revealing the paradigm shift that occurred in-between the emergence of Modernism in pre-war Europe and its transition to Post-Modernism in the second half of the 20th c., as a largely American issue. The success and influence of the magazine was due to the resources of its parent corporations, F.W. Dodge and McGraw-Hill, its support and acknowledgement by professional and academic organizations and the connections, commitment and inventiveness of its editors. The editorial campaigns of the magazine trace the struggle for the adaptation of the modern movement in the American context and through that to its subsequent global eminence as “contemporary architecture,” a term popularised by the Record.